Evaluation of Etest Method for Determining Voriconazole and Amphotericin B MICs for 162 Clinical Isolates of Cryptococcus neoformans - Maxwell, M. J. (American Society for Microbiology, 2003)
The performance of the Etest for voriconazole and amphotericin B susceptibility testing of 162 isolates of Cryptococcus neoformans was assessed against the National Committee for Clinical Laboratory Standards (NCCLS) broth microdilution method. The NCCLS method employed RPMI 1640 broth medium, and MICs were read after incubation for 72 h at 35°C. MICs were determined by Etest for all 162 isolates with RPMI 1640 agar containing 2% glucose (RPG agar) and were read after incubation for 72 h at 35°C. The Etest results for both voriconazole and amphotericin B correlated well with reference MICs. Agreement was 94% for voriconazole and 99% for amphotericin B. When discrepancy was noted between the results obtained by Etest and broth microdilution for voriconazole, the Etest generally provided a higher MIC. The Etest method using RPG agar appears to be a useful method for determining the susceptibility of C. neoformans to voriconazole and amphotericin B.